GAMBARAN KADAR KOLESTEROL TOTAL PENDERITA DIABETES MELLITUS DI RUMAH SAKIT BENYAMIN GULUH KOLAKA - firdayanti Firdayanti; Angriani Fusvita; Irdayanti Irdayanti (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2022)
Diabetes mellitus is a hyperglycemia disease charactherized by absolute absence of insulin or a relative decrease in insulin insensitivity to insulin., diseases of the eyes, kidneys and nerves. Cholesterol and diabetes mellitus have a related , where factors that can increase total cholesterol (hyperglycemia), namely nutrition, drugs, obesity and age are also factors that cause a person suffering from diabetes mellitus. This study aims to determine the picture of total cholesterol levels in people with diabetes mellitus in Benyamin guluh hospital Kolaka. The sample taken in this study is the outpatient plasma at the Benyamin guluh hospital Kolaka that was diagnosed with diabetes mellitus. In this study the number of samples studied were 30 samples as many as 30 people were obtained by accidental sampling . The results of the study were from the examination of 30 patiens with diabetes mellitus at Benyamin Guluh Kolaka Hospital. Normal kolesterol result were 11 people (37%), and abnormal 19 people (30%). Keywords : Diabetes mellitus, Total cholesterol levels, Hyperglycemia